Cell Death or Survival Promoted by Alternative Isoforms of ErbB4 - Sundvall, Maria (The American Society for Cell Biology, 2010)
The significance of ErbB4 in tumor biology is poorly understood. The ERBB4 gene is alternatively spliced producing juxtamembrane (JM-a and JM-b) and cytoplasmic (CYT-1 and CYT-2) isoforms. Here, signaling via the two alternative ErbB4 JM isoforms (JM-a CYT-2 and JM-b CYT-2) was compared. Fibroblasts expressing ErbB4 JM-a demonstrated enhanced ErbB4 autophosphorylation, growth, and survival. In contrast, cells overexpressing ErbB4 JM-b underwent starvation-induced death. Both pro- and antisurvival responses to the two ErbB4 isoforms were sensitive to an ErbB kinase inhibitor. Platelet-derived growth factor receptor-alpha (PDGFRA) was identified as an ErbB4 target gene that was differentially regulated by the two ErbB4 isoforms. The soluble intracellular domain of ErbB4, released from the JM-a but not from the JM-b isoform, associated with the transcription factor AP-2 and promoted its potential to enhance PDGFRA transcription. Survival of cells expressing JM-a was suppressed by targeting either PDGFR-α or AP-2, whereas cells expressing JM-b were rescued from cell death by the PDGFR-α agonist, PDGF-BB. These findings indicate that two alternative ErbB4 isoforms may promote antagonistic cellular responses and suggest that pharmacological inhibition of ErbB4 kinase activity may lead to either suppression or promotion of cellular growth.